POLICIES FOR ENHANCING PROFESSIONAL COMPETENCE AND LEGAL ETHICS OF LAWYERS: SINGAPORE’S EXPERIENCE AND LESSONS FOR VIETNAM - Tran, Dao Viet Hung; Pham, Phuong Linh (JILPR Journal Indonesia Law and Policy Review, 2026)
In the context of national renewal and deep international integration, the demand for high-quality legal services in Vietnam has increased significantly. Responding to this requirement, the Communist Party of Vietnam promulgated Resolution No. 66-NQ/TW on renewing law-making and law enforcement to meet the demands of national development in the new era, emphasizing breakthrough solutions to enhance the quality of legal human resources. As an integral component of this workforce, Vietnamese lawyers must strengthen both professional competence and ethics to deliver effective and credible legal services. However, current lawyer training programs in Vietnam reveal notable shortcomings, particularly in integrating theoretical knowledge with practical skills and fostering ethical values. Employing a comparative research approach, this study examines Singapore’s experience in lawyer training - a well-developed and practice-oriented legal education system. On this basis, the paper identifies key lessons and proposes feasible solutions to improve the quality of lawyer training in Vietnam, aligning it with international standards and domestic development needs.